1, 3-Propanediol production by a newly isolated strain, Clostridium perfringens GYL. (June 2017) - Guo, Yali; Dai, Lu; Xin, Bo; Tao, Fei; Tang, Hongzhi; Shen, Yaling; Xu, Ping
Highlights: A new 1, 3-propanediol (1, 3-PD) producer Clostridium perfringens GYL was isolated. Strain GYL has a fast growth speed and high productivity of 1, 3-PD (2.0 g/(L·h)). Strain GYL could tolerate high concentrations of glycerol up to 200 g/L. Abstract: 1, 3-Propanediol (1, 3-PD), a valuable bulk industrial material, has attracted increasing interest in recent years. A novel strain GYL isolated from soil samples could efficiently convert glycerol to 1, 3-PD anaerobically. The physiological and biochemical characteristics of strain GYL were determined, indicating that strain GYL is a member of Clostridium perfringens with the neighbor-joining method of 16S rRNA gene sequences. The fermentation properties of strain GYL were also investigated systematically, which showed that the strain has a fast growth speed and high tolerance to 200 g/L glycerol. Batch fermentation was carried out at a high glycerol concentration of 100 g/L, and strain GYL produced 36.7 g/L 1, 3-PD. In fed-batch fermentation, strain GYL showed a maximum productivity of 2.0 g/(L·h), and produced 40.0 g/L 1, 3-PD, with a high yield of 0.68 mol 1, 3-PD/mol glycerol. This study shows that the newly isolated strain GYL may have potential for 1, 3-PD production from glycerol.